2016
DOI: 10.1242/jcs.187922
|View full text |Cite
|
Sign up to set email alerts
|

Collective migration and cell jamming in asthma, cancer and development

Abstract: Collective cellular migration within the epithelial layer impacts upon development, wound healing and cancer invasion, but remains poorly understood. Prevailing conceptual frameworks tend to focus on the isolated role of each particular underlying factor -taken one at a time or at most a few at a time -and thus might not be tailored to describe a cellular collective that embodies a wide palette of physical and molecular interactions that are both strong and complex. To bridge this gap, we shift the spotlight t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
176
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 155 publications
(178 citation statements)
references
References 85 publications
2
176
0
Order By: Relevance
“…Here we identified that a physical boundary is sufficient to trigger differentials of cellular forces and deformations, and that jamming is sufficient to control the dynamics of those differentials. Our findings thus raise the possibility that rather than being solely controlled by genetic clocks and travelling waves of biochemical nature, tissue segregation and patterning during development and homeostasis is controlled by cell jamming 57 .…”
mentioning
confidence: 87%
“…Here we identified that a physical boundary is sufficient to trigger differentials of cellular forces and deformations, and that jamming is sufficient to control the dynamics of those differentials. Our findings thus raise the possibility that rather than being solely controlled by genetic clocks and travelling waves of biochemical nature, tissue segregation and patterning during development and homeostasis is controlled by cell jamming 57 .…”
mentioning
confidence: 87%
“…Dynamic cell -cell junctions enable cells to change position relative to their neighbors or as multicellular groups; they are relevant during morphogenesis and phases of tissue activation, for example, in response to injury or inflammation (Collins and Nelson 2015). By regulating junction "fluidity," the ag-gregate state and dynamics of cells can change remarkably and, accordingly, alter collective functions (Collins and Nelson 2015;Park et al 2016).…”
mentioning
confidence: 99%
“…There are increasing recognition that this non-local cooperative process can be explained by the concept of jamming which have been proposed at the soft matter physics. Similarly to close-packed inert particulate matter, the increase or decrease in cell-cell adhesion would promote jamming or unjamming transition in the confluent living cellular layer2728. In the context of jamming transition, we found that HGF interfered with the jamming of the cell collectives and promoted the expansion of a confluent layer by changing the cell-cell adhesive stresses and kinematic behaviors, consistently with the cellular “unjamming”.…”
Section: Discussionmentioning
confidence: 63%